2014
DOI: 10.1016/j.yebeh.2014.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Severe hippocampal atrophy is not associated with depression in temporal lobe epilepsy

Abstract: Depression in temporal lobe epilepsy (TLE) is common, is a strong predictor of subjective disability, and may have unique pathophysiological characteristics. Previous studies showed that reduced hippocampal volume is associated with significant depressive symptoms in TLE patients. We utilized regions of interest analysis of high-resolution brain MRI and a reliable and valid measure of depressive symptoms to evaluate 28 consecutive adult subjects with video/EEG confirmed TLE. Regions of interest were based on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The observation that the dBNST is enlarged in the TLE patients in this study is contrary to the decrease in gray matter volume and neuron loss commonly seen in other major structures commonly seen to be morphologically abnormal in TLE patients, such as the hippocamus 35 . In our study, we find that hippocampal sclerosis seen in many of our TLE patients is not associated with the presence of depression, a finding that is consistent with other studies demonstrating the lack of a relationship between hippocampal sclerosis and decreased hippocampal volume with depression 36 . Furthermore, the hippocampal sclerosis is not associated with the enlargement of the dBNST, suggesting that whereas the dBNST may be a part of the neural network involving depression in TLE, the hippocampus is not.…”
Section: Discussionsupporting
confidence: 91%
“…The observation that the dBNST is enlarged in the TLE patients in this study is contrary to the decrease in gray matter volume and neuron loss commonly seen in other major structures commonly seen to be morphologically abnormal in TLE patients, such as the hippocamus 35 . In our study, we find that hippocampal sclerosis seen in many of our TLE patients is not associated with the presence of depression, a finding that is consistent with other studies demonstrating the lack of a relationship between hippocampal sclerosis and decreased hippocampal volume with depression 36 . Furthermore, the hippocampal sclerosis is not associated with the enlargement of the dBNST, suggesting that whereas the dBNST may be a part of the neural network involving depression in TLE, the hippocampus is not.…”
Section: Discussionsupporting
confidence: 91%
“…Shamim [32] and Baxendale [25] found that in those patients with right TLE and depression (regardless of whether HS was present) there were also reduced contralateral (left) hippocampal volumes compared to patients without concomitant depression. However, this finding was not replicated in a later study by Hecimovic et al 2014 [33] who found larger hippocampal volumes in those patients with TLE and depression compared to those without depression. Richardson and collaborators [34] found larger amygdala volumes in patients with TLE and depression as compared to patients without depression.…”
Section: Structural Neuroimagingmentioning
confidence: 76%
“…75 The severity of depression is associated with the risk of epilepsy. 76 Depression and suicidality tend to be more prominent in individuals with TLE compared with those who have genetic generalized epilepsies, 77,78 and within TLE, depression severity correlates with pharmacoresistance but does not correlate with the side 57 or the extent of hippocampal atrophy, 79 if present. Improvements in depression that follow temporal lobectomy are strongly associated with improvements in seizure control.…”
Section: Autoimmune Epilepsiesmentioning
confidence: 99%